Hubungan Kualitas Tidur dengan Fungsi Kognitif Mahasiswa Fakultas Kedokteran - Wardah Nurul 'Izza; Yuli Susanti; Purnomo (Bandung Conference Series: Medical Science, 2024)
Abstract. Academic workload in medical school has an influence on sleep quality, resulting high incidence of poor sleep quality in medical students. This study aims to determine the correlation between sleep quality and cognitive function among medical students in Faculty of Medicine, Bandung Islamic University 2022/2023 academic year. One hundred and five respondents were selected by consecutive sampling technique. Sleep quality was assessed by Pittsburgh Sleep Quality Index (PSQI) questionnaire and cognitive function was assessed by MoCA-INA. This research used an observational analytical method with cross sectional approach and statistical analysis using the Chi-square test. The results showed that medical students in Faculty of Medicine mostly had poor sleep quality (54,3%) and had normal cognitive function (68,6%). Out of 48 students with good sleep quality, 40% students had normal cognitive function and 5,71% students had abnormal cognitive function. Then, out of 57 students with poor sleep quality, 28,57% students had normal cognitive function and 25,71% students had abnormal cognitive function. A correlation (p-value= 0,000) was found between sleep quality and cognitive performance. Hence, there is correlation between sleep quality with cognitive function among medical students in Faculty of Medicine, Bandung Islamic University 2022/2023 academic year. There is an interaction between biological, psychological, and social mechanisms on cognitive dysfunction (especially in the prefrontal cortex) due to poor sleep quality. Abstrak. Beban belajar yang tinggi di fakultas kedokteran memiliki pengaruh terhadap kualitas tidur, sehingga menimbulkan kejadian kualitas tidur yang buruk pada mahasiswa fakultas kedokteran. Penelitian ini bertujuan untuk mengetahui hubungan antara kualitas tidur dengan fungsi kognitif pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung tahap akademik tahun ajaran 2022/2023. Pemilihan sampel pada penelitian ini menggunakan teknik consecutive sampling dengan 105 mahasiswa sebagai subjek penelitian. Penilaian kualitas tidur dilakukan melalui kuesioner Pittsburgh Sleep Quality Index(PSQI) dan penilaian fungsi kognitif menggunakan instrumen MoCA-INA. Penelitian ini menggunakan metode analitik observasional dengan pendekatan cross sectional dan analisis statistik berupa uji Chi-square. Hasil penelian ini menunjukkan bahwa mahasiswa Fakultas Kedokteran Universitas Islam Bandung sebagian besar memiliki kualitas tidur yang buruk (54,3%) dan memiliki fungsi kognitif normal (68,6%). Dari total 48 mahasiswa dengan kualitas tidur baik, sebanyak 40% mahasiswa memiliki fungsi kognitif normal dan 5,71% mahasiswa memiliki fungsi kognitif abnormal. Kemudian, dari total 57 mahasiswa dengan kualitas tidur buruk, sebanyak 28,57% mahasiswa memiliki fungsi kognitif normal dan 25,71% mahasiswa memiliki fungsi kognitif abnormal. Hasil analisis hubungan kualitas tidur dengan fungsi kognitif didapatkan p-value= 0,000. Penelitian ini menyimpulkan bahwa kualitas tidur memiliki hubungan terhadap fungsi kognitif mahasiswa Fakultas Kedokteran Universitas Islam Bandung tahap akademik tahun ajaran 2022/2023. Terdapat interaksi antara mekanisme biologis, psikologis, dan sosial yang terlibat dalam disfungsi kognitif (terutama pada area prefrontal cortex) akibat kualitas tidur yang buruk.